Safety-Management Practices and the Occurrence of Occupational Accidents: Assessing the Mediating Role of Safety Compliance - Ajmal, M. (MDPI, 2022)
This study examines the impact of critical safety-management practices on the occurrence of occupational accidents by means of safety compliance in Malaysiaâs oil and gas industry. This study employed a cross-sectional design, in which data were collected from oil and gas downstream operations in five states within Malaysia using the convenience-sampling technique. The valid data of 280 responses were analyzed with Smart-PLS, and the structural-equation-modeling technique was applied. The studyâs outcome revealed that safety-management practices (i.e., safety training, workersâ involvement, safety communication and feedback, management commitment to safety, safety-promotion policies, and safety rules and procedures) were significantly associated with occupational accidents via safety compliance. Thus, this study is helpful for practitioners and researchers to understand the importance of safety-management practices in reducing occupational accidents. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.